2013
DOI: 10.1021/jo401683r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Thermochemiluminescent Acridine-Containing 1,2-Dioxetanes as Promising Ultrasensitive Labels in Bioanalysis

Abstract: Thermochemiluminescence is the luminescence process in which a thermodynamically unstable molecule decomposes with light emission when heated above a threshold temperature. We recently reported the thermochemiluminescence properties of an acridine-containing 1,2-dioxetane, which emits at relatively low temperatures (i.e., below 100 °C). Herein, we explored the effect of the introduction of methyl substituents in the acridine system. The methyl group did not determine an excessive destabilization of 1,2-dioxeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…2 h , entry 2, Table ) . The observed behavior also proved to be peculiar in comparison with the fluorescence quantum yield trend previously recorded for (poly)methylated acridones . In the presence of EDGs, the φ F values showed an increase for substitution at both the 2‐ and 3‐positions.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…2 h , entry 2, Table ) . The observed behavior also proved to be peculiar in comparison with the fluorescence quantum yield trend previously recorded for (poly)methylated acridones . In the presence of EDGs, the φ F values showed an increase for substitution at both the 2‐ and 3‐positions.…”
Section: Resultsmentioning
confidence: 55%
“…Conversely, 3,6‐difluoro‐ ( 2 h ) and 1,6‐difluoro‐substituted ( 2 i ) acridones showed decreased fluorescence quantum yields, but the corresponding dioxetanes 4 h – i displayed significantly longer half‐life values. A comparison of these data with those recorded for methyl‐substituted acridan‐based dioxetanes confirmed that the introduction of weak EDGs increased the ketone fluorescence quantum yield and lowered the dioxetane activation energy, regardless of the position on the aromatic ring. On the contrary, the impact of fluorine atoms depended dramatically on the substituent position.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations